Modelling of Surface Roughness and Tool Consumption of WEDM and Optimization of Process Parameters Based on Fuzzy-PSO. (2018) - Choudhuri, Bikash; Sen, Ruma; Kumar Ghosh, Subrata; Saha, S.C.
Abstract: Wire electric discharge machining (WEDM) has become a popular machining processes for electrically conductive materials. However, it suffers from few limitations such as poor surface finish and high tool cost that effects the quality and productivity of finished product. To overcome these, an attempt has been employed to model the performances of WEDM process on H21 tool steel using response surface methodology. The effect of various process parameters (pulse on time, pulse off time, current, gap voltage and wire tension) on the performance characteristics of WEDM is studied. Analysis of variance is performed to identify the significant factors. It is revealed that pulse on time is the predominant factor that influences the machining characteristics. The fuzzy logic methodology applied to solve multiple responses characteristics problem, particle swarm optimization algorithm applied to optimize and enhance the performance of WEDM process. Energy dispersive x-ray shows high amount of carbon and oxygen content on optimum cut machined surface.